Pengaruh Gaya Kepemimpinan dan Motivasi terhadap Kinerja Karyawan pada PT. Indomarco Prismatama Tbk. Cabang Jember - Lutfi, Jihad; Feranita, Nungky Viana (Majalah Ilmiah DIAN ILMU, 2023)
Leadership style and motivation have an important role to achieve organizational and corporate goals. Thus, human resources who have obtained the right leadership style and work motivation will experience increased performance from workers. This study aims to analyze the influence of leadership style and motivation on the performance of employees of PT. Indomarco Prismatama Jember Branch simultaneously or partially. The research method uses quantitative methods and the population is employees of PT. Indomarco Prismatama Jember Branch. The sampling technique used accidental sampling with a total of 80 respondents. The method used to perform the analysis is multiple liner analysis using SPSS 22.0 for windows software. The result of the research is that leadership style and motivation have a simultaneous influence on the performance of employees at PT. Indomarco Prismatama Jember. In addition, leadership style has a significant effect on employee performance, but motivation has no partial effect on employee performance.